Issues of terrorism on the internet in the wave of democratization of post-reform Indonesia: A semiotic analysis - Saifullah, Aceng Ruhendi (Indonesian Journal of Applied Linguistics, 2016)
The discourse of terrorism is a global issue but tends to be interpreted as controversial. This study sought to dismantle the controversy of meanings through the analysis of signs and meanings, with a view to explore and demonstrate the wave of democratization that took place in post-reform era in Indonesia. This study was a case study using readers’ responses to terrorism issues provided by cyber media on the Internet. It also rests primarily on the semiotic theory of Peirce and the concept of democratization of Huntington. The results showed that participation, freedom of expression, and equal power relations occurred in the interactive discourse in the cyber news media in the form of a dialogue between the responders, the media, and the debate among the responders. Responders tended to argue that signs and meanings are constructed by the media and to interpret information about terrorism as "political engineering" which was expressed by means of emotive tone. Meanwhile, the media tended to construct a "political imagery" which was expressed in a confrontational way, and the resources tended to understand it as "noise level of political elite ", which was expressed in a persuasive manner. Such differences occurred due to the factors of media context that tended to be "convivial" and the context of the communication situation on the Internet that tends to show "discretion". Based on these findings, this study concluded that interactive discourse in the Internet can be formulated as a democratic forum as the meaning making of the text is no longer dominated by media and the sources of information, but tend to be shared with the public. However, in terms of discourse process, interactive discourse in cyber media tends to be anarchic because the tone of interaction tends to be little, the relationship patterns tend to center on and be dominated by responders, the identities of responders tend to be anonymous, and linguistic expressions of the responders tend to be emotive.